Patient experiences in behavioral health integrated primary care settings: the role of stigma in shaping patient outcomes over time. Issue 10 (26th November 2019) - Royal Kenton, Natalie; Broffman, Lauren; Jones, Kyle; Albrecht Mcmenamin, Kayla; Weller, Maggie; Brown, Kristin; Currier, Jessica; Wright, Bill
ABSTRACT: Behavioral health integration (BHI) models seek to improve patient experience and outcomes by bridging physical and behavioral health services. Past BHI research has not focused on stigma in these settings, which has been previously found to impact patient engagement and outcomes. We surveyed patients over a two year period at 12 integrated clinics in Oregon using measures developed by a Patient Advisory Team. Over a quarter of respondents reported stigmatization (26.81%). Compared to non-stigmatized patients, those who reported stigma had five times the odds of reporting unmet health needs (OR=5.14, p<0.0001), three times the odds reporting issues accessing care (OR=2.93, p<0.0001), six times the odds reporting hassle to get care (OR=6.49, p<0.0001), and three times the odds of reporting poor communication between providers (OR=3.45, p<0.0001). After examining the interaction between stigmatization and time, we found that stigmatized patients had lower odds at year two of reporting unmet health needs (OR=0.68, p=0.0034), issues accessing care (OR=0.77, p=0.0400), hassle getting care (OR=0.57, p=0.0001), and poor provider communication (OR=0.77, p=0.0544). We found that stigma remained prevalent for patients seeking care in the integrated clinics studied despite integration. Systems should consider integration efforts and reducing stigmatizing experiences in tandem to truly improve patient outcomes.